County Population Estimates (Experimental) by Age, Sex, and Race: 1980, 1982 and 1984 ([Verlag nicht ermittelbar], 1988)
This file provides county population estimates by age (18 age groups), sex, and race (White, Black, and other races) for July 1st of 1980, 1982, and 1984. The estimates make full use of 1980 census data on gross in- and out- migration for counties and replace the estimates previously labeled "provisional." Data is supplied for each of the 3,136 United States counties and county equivalents as defined in the 1980 census.